Whole grain intake, determined by dietary records and plasma alkylresorcinol concentrations, is low among pregnant women in Singapore - Ross, Alastair B; Colega, Marjorelee T; Lim, Ai Lin; Silva-Zolezzi, Irma; Macé, Katherine; Saw, Seang Mei; Kwek, Kenneth; Gluckman, Peter; Godfrey, Keith M; Chong, Yap-Seng; Chong, Mary F F (Asia Pacific journal of clinical nutrition, 2015)
Background and Objectives: To quantify whole grain intake in pregnant women in Singapore in order to provide the first detailed analysis of whole grain intake in an Asian country and in pregnant women. Methods and Study Design: Analysis of 24-h diet recalls in a cross-sectional cohort study and analysis of a biomarker of whole grain intake (plasma alkylresorcinols) in a subset of subjects. The Growing Up in Singapore Towards healthy Outcomes-mother offspring cohort study based in Singapore. 998 pregnant mothers with complete 24-h recalls taken during their 26-28th week of gestation. Plasma samples from a randomly select subset of 100 subjects were analysed for plasma alkylresorcinols. Results: Median (IQR) whole grain intake for the cohort and the 30% who reported eating whole grains were 0 (IQR 0, 9) and 23.6 (IQR 14.6, 44.2) g/day respectively. Plasma alkylresorcinol concentrations were very low [median (IQR)=9 (3, 15) nmol/L], suggesting low intake of whole grain wheat in this population. Plasma alkylresorcinols were correlated with whole grain wheat intake (Spearman's r=0.35; p<0.01). Conclusions: Whole grain intake among pregnant mothers in Singapore was well below the 2-3 (60-95 g) servings of whole grains per day recommended by the Singapore Health Promotion Board. Efforts to increase whole grain intake should be supported to encourage people to choose whole grains over refined grains in their diet.